Managerial Performance of Fast-Food Restaurant Managers in the Philippines: Basis for Capability Enhancement Program (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study generally assessed the management skills, work values, and job performance of the fast-food restaurant managers in the Philippines as a basis for developing managerial capability enhancement program. Specifically, it aims to determine the profile; the level of the management skills, work values, and job performance as assessed by the managers and of their staff; and the relationship that exists among the variables: profile and management skills, profile and work values, profile and job performance, management skills and job performance, and work values and job performance. The results revealed that most managers ages 25 and below and with bachelor's degree; they mostly served as a manager for only five years and below; had attended five and below the number of trainings relative to their position; and have an average monthly income of P15,000 and below. Managers are excellent in management skills, work values, and job performance as assessed by themselves and their staff. Results also showed that the average monthly income was found to have a significant relationship with management skills, work values, and job performance. Further, management skills and work values are highly significant to the fast-food restaurant managers' job performance.